Penerapan Model Pembelajaran Together Win dan STAD untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Putri Mahanani (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: The objectives of this study are: (1) to describe the application of the Together Win (TW) and STAD learning models; (2) describe the differences in student learning outcomes as a result of the application of the Together Win (TW) and STAD learning models. This study was designed using quantitative quasi-experimental research. The research procedures are: (1) pre-test before learning activities; (2) giving treatment of Together Win (TW) and STAD learning models to elementary school students; (3) post-test. The next analysis uses the SPSS program with the t-test analysis technique. The results of the research conducted indicate that the Together Win (TW) and STAD learning models have been carried out in accordance with the steps of their activities. In the use of the STAD learning model, student learning outcomes on cognitive aspects, the percentage of completeness is 65%. Psychomotor aspects are 85% and affective aspects, the percentage of completeness is 50%. While the completeness of student learning outcomes on cognitive aspects that use the Together Win (TW) model is 90%. Psychomotor aspects are 85% and affective aspects are 90%. The results of the t-test using SPSS based on comparisons of t-tables, it was concluded that the TW learning model was more effective than the STAD model. Abstrak: Tujuan penelitian ini adalah: (1) mendeskripsikan penerapan model pembelajaran Together Win (TW) dan STAD; (2) mendeskripsikan perbedaan hasil belajar siswa sebagai akibat penerapan model pembelajaran Together Win (TW) dan STAD. Penelitian ini dirancang dengan menggunakan penelitian kuantitatif kuasi eksperimen. Prosedur penelitiannya yaitu: (1) pre-test sebelum kegiatan pembelajaran; (2) pemberian perlakuan model pembelajaran Together Win (TW) dan STAD pada siswa sekolah dasar (SD); (3) post-test. Analisis selanjutnya menggunakan program SPSS dengan teknik analisis t-test. Hasil penelitian yang dilaksanakan menunjukkan bahwa model pembelajaran Together Win (TW) dan STAD telah dilaksanakan sesuai dengan langkah kegiatannya. Pada penggunaan model pembelajaran STAD, hasil belajar siswa pada aspek kognitif, persentase ketuntasannya 65%. Aspek psikomotor sebesar 85% dan aspek afektif, persentase ketuntasannya sebesar 50%. Sedangkan ketuntasan hasil belajar siswa pada aspek kognitif yang menggunakan model Together Win (TW) sebesar 90%. Aspek psikomotor sebesar 85% dan aspek afektif sebesar 90%. Hasil t-test dengan menggunakan SPSS berdasarkan perbandingan t-hitung dengan t-tabel, maka disimpulkan bahwa model pembelajaran TW lebih efektif daripada model STAD.